1997
DOI: 10.1152/ajpheart.1997.273.4.h1754
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of arrhythmias and heart rate variability in wild-type rats exposed to social stress

Abstract: Psychological stressors of different natures can induce different shifts of autonomic control on cardiac electrical activity, with either a sympathetic or a parasympathetic prevalence. Arrhythmia occurrence, R-R interval variability, and plasma catecholamine elevations were measured in male wild-type rats exposed to either a social stressor (defeat) or a nonsocial challenge (restraint). Electrocardiograms were telemetrically recorded, and blood samples were withdrawn through jugular vein catheters from normal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
118
1
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(130 citation statements)
references
References 24 publications
9
118
1
2
Order By: Relevance
“…Thus, the link between inflammatory processes and negative and competitive social interactions may also be mediated by an increase in prolactin or CRH in response to stress. Negative social interactions also lead to increases in blood pressure and heart rate (43,44), indices of activity of the autonomic nervous system, which is consistent with rodent models showing that social stress increases sympathetic activity (45). Given that sympathetic activity is positively related to inflammation, whereas parasympathetic activity is inversely related to inflammation (46,47), it is plausible that negative and competitive daily social interactions up-regulate inflammatory activity via the autonomic nervous system.…”
Section: Discussionsupporting
confidence: 68%
“…Thus, the link between inflammatory processes and negative and competitive social interactions may also be mediated by an increase in prolactin or CRH in response to stress. Negative social interactions also lead to increases in blood pressure and heart rate (43,44), indices of activity of the autonomic nervous system, which is consistent with rodent models showing that social stress increases sympathetic activity (45). Given that sympathetic activity is positively related to inflammation, whereas parasympathetic activity is inversely related to inflammation (46,47), it is plausible that negative and competitive daily social interactions up-regulate inflammatory activity via the autonomic nervous system.…”
Section: Discussionsupporting
confidence: 68%
“…In rats, it has been shown that during a social defeat, the heart rate increases due to shift in the autonomic balance toward a higher sympathetic activity, and that ventricular arrhythmias occur frequently (Sgoifo et al 1994(Sgoifo et al , 1997. In pigs, it was shown that when using electrophysiological stimulation of ventricular tachycardias, social stress facilitates arrhythmogenesis (Kirby et al 1991).…”
mentioning
confidence: 99%
“…However, it is unknown whether acute social stress induces ventricular arrhythmias during normal husbandry practice. Ventricular arrhythmias are risk markers for sudden cardiac death, and an increased occurrence of arrhythmias is related to high sympathetic activity (Verrier and Lown 1987;Kirby et al 1991;Sgoifo et al 1997). Therefore, heart rate, indices of the autonomic balance and the incidence of cardiac arrhythmias may be sensitive indicators of the level of stress and thus measures of pig welfare.…”
mentioning
confidence: 99%
“…The same can be observed in a comparison between strains. The aggressive wild-type rats responded to social defeat with larger sympathetic (plasma noradrenalin levels) reactivity and concomitantly lower parasympathetic reactivity (as measured by increased heart rate response and decreased heart rate variability) than the less aggressive Wistar rats (Sgoifo et al, 1997). Thus, proactive coping rodents show in response to stressful stimulation a low Hypothalamus-Pituitary-Adrenocortical (HPA) axis reactivity (low plasma corticosterone response) but high sympathetic reactivity (high levels of catecholamines).…”
Section: Neuroendocrinology Of Coping Strategiesmentioning
confidence: 99%
“…Because of the role of the two branches of the autonomic nervous system in cardiovascular control, one may expect a differential vulnerability for various types of cardiovascular pathology as well. Indeed, a number of experiments found evidence that the proactive coping animal is more vulnerable to develop hypertension, atherosclerosis, and tachyarrhythmia due to the high sympathetic reactivity (Fokkema, Koolhaas, & Gugten, 1995;Fokkema, Smit, Van der Gugten, & Koolhaas, 1988;Manuck, Kaplan, & Clarkson, 1983;Sgoifo, De Boer, Haller, & Koolhaas, 1996;Sgoifo et al, 1997). However, it seems that these types of cardiovascular pathology only develop under conditions of threat to control rather than loss of control (Koolhaas & Bohus, 1991).…”
Section: Cardiovascular Pathologymentioning
confidence: 99%